Teachers’ Pedagogical Practices in Relation to Students’ Motivation in Blended Learning - Mhie B. Daniel; Haydee D. Villanueva (PT ARRUS Intelektual Indonesia, 2023)
The emergence of the new normal in education has brought about the need for effective classroom management strategies from teachers and an unwavering commitment to learning from students. In light of this, this study aimed to investigate the relationship between teachers' pedagogical practices and students' motivation in a blended learning setting. The research was conducted at Misamis University in Ozamiz City, utilizing a descriptive-correlational research design. The study involved 120 students who were selected through purposive and quota sampling techniques. To gather the necessary data, researcher-made questionnaires on Teachers' Pedagogical Practices and Students' Motivation in Blended Learning were administered. The data were then analyzed using mean and standard deviation as well as Pearson Product-Moment Correlation Coefficient. The results revealed that teachers' pedagogical practices in blended learning were of a very high standard, with students reporting a correspondingly high level of motivation in the modality. The findings suggest that teachers have made a concerted effort to adapt to the new learning modality and that blended learning has been successful in motivating college students. In light of the study's findings, it is recommended that teachers continue to innovate and refine their pedagogical practices in blended learning to maintain high levels of student motivation in the teaching-learning process.